Clinical Application of Thiopurine Pharmacogenomics in Pediatrics - Pavlovic, Sonja; Kotur, Nikola; Stankovic, Biljana; Gasic, Vladimir; Lucafo, Marianna; Decorti, Giuliana; Zukic, Branka (Current Drug Metabolism, 2020)
Background: Thiopurine drugs are used for the treatment of pediatric diseases. Inter-individual differences in the metabolism of these drugs greatly influence the risk of thiopurine induced toxicity and therapy failure. These differences are the consequence of genomic, epigenomic and transcriptomic variability among patients. Pharmacogenomics aims to individualize therapy according to the specific genetic signature of a patient. Treatment protocols based on thiopurine drugs have already been improved by applying pharmacogenomics in pediatric clinical practice. Objective: The aim of this review was to summarize the application of thiopurine pharmacogenomics in pediatric patients suffering from acute leukemias, different types of autoimmune and inflammatory diseases, as well as in posttransplant care. Methods: We searched PubMed/Medline database to identify thiopurine pharmacogenomic markers clinically relevant in pediatric diseases. Results: TPMT and NUDT15 pharmacogenomic testing is done in pediatric care, contributing to the reduction of thiopurine induced toxicity. Data on numerous novel potential pharmacogenomic markers relevant for optimization of thiopurine treatment are still controversial (ITPA, ABCC4, NT5C2, PRPS1, GSTM1, FTO gene variants). Majority of evidences regarding thiopurine pharmacogenomics in pediatrics have been acquired by studying acute lymphoblastic leukemia and inflammatory bowel disease. For other pediatric diseases, namely acute myeloid leukemia, non-Hodgkin lymphoma, juvenile idiopathic arthritis, atopic dermatitis, juvenile autoimmune hepatitis and renal allograft transplantation, data are still scarce. Conclusion: Thiopurine pharmacogenomics has shown to be one of the best examples of successful application of pharmacogenomics in pediatrics.
Keywords: Thiopurine drugs